Do firms' relationships with principal customers/suppliers affect shareholders' income? - Wang, Jin (Journal of Corporate Finance, 2012)
In this paper, we examine whether a firm's relationship with its principal customers/suppliers affects its payout policies. A firm has customer–supplier relationships when its business depends on a small number of major customers/suppliers. The extant literature indicates two channels through which customer–supplier relationships might negatively affect a firm's dividend payments: 1) the high financial distress costs associated with relationship-specific investments and 2) the information certification effect of the principle customer. Consistent with expectations, our study reveals a negative relationship between a firm's dependence on customer–supplier relationships and its dividend payments. This result is robust to various model specifications and consistent with evidence regarding the time-series properties of dividends. Moreover, we find that high financial distress costs associated with relationship-specific investments are the key channel through which a firm's customer–supplier relationship affects its dividend payments. Overall, our results suggest that a firm's relationship with its non-financial stakeholders, such as principal customers/suppliers, is an important determinant of its shareholders' income.